(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Aging is not a disease but it a changes that come with time, aging may make an individual susceptible to disease. Exposure to smoke, UV radiation, chemicals or other exogenous agents over time can damage cells, as can produce DNA replication errors or oxidative stress. The use of antioxidant curcumin can produce intracellular defenses in addition to low expensive and no side effect. In the present study, hydrogen peroxide (H2O2) was used to produce oxidative stress in Human Fibroblast cell lines (HFB4) and free curcumin and niosome entrapping curcumin treatments are used for aged HFB4 cell lines. Using Flowcytometry analysis, p 16 INK4a and p53 BP1 genes levels were investigated as aging biomarkers. Result show that H2O2 treated cell lines are highly elevate p16 INK4a and p53 BP1 genes. While HFB4 cells treated with free curcumin and niosome entrapping curcumin were significantly protected against aged process.